Intravitreal melphalan hydrochloride vs propylene glycol-free melphalan for retinoblastoma vitreous seeds: Efficacy, toxicity and stability in rabbits models and patients. (March 2021) - Bogan, Carley M.; Pierce, Janene M.; Doss, Stephanie D.; Tao, Yuankai K.; Chen, Sheau-chiann; Boyd, Kelli L.; Liao, Albert; Hsieh, Terry; Abramson, David H.; Francis, Jasmine H.; Friedman, Debra L.; Richmond, Ann; et al.
Abstract: The use of intravitreal chemotherapy has revolutionized the treatment of advanced intraocular retinoblastoma, as intravitreal melphalan has enabled difficult-to-treat vitreous tumor seeds to be controlled, leading to many more eyes being saved. However, melphalan hydrochloride (MH) degrades rapidly in solution, increasing logistical complexity with respect to time between medication preparation and administration for intravitreal administration under anesthesia for retinoblastoma. A new propylene glycol-free melphalan (PGFM) formulation has greater stability and could therefore improve access and adoption of intravitreal chemotherapy, allowing more children to retain their eye(s). We compared the efficacy and toxicity of both formulations, using our rabbit xenograft model and clinical patient experience. Three weekly 12.5 μg intravitreal injections of MH or PGFM (right eye), and saline (left eye), were administered to immunosuppressed rabbits harboring human WERI-Rb1 vitreous seed xenografts. Residual live cells were quantified directly, and viability determined by TUNEL staining. Vitreous seeds were reduced 91% by PGFM (p = 0.009), and 88% by MH (p = 0.004; PGFM vs. MH: p = 0.68). All residual cells were TUNEL-positive (non-viable). In separate experiments to assess toxicity, three weekly 12.5 μg injections of MH, PGFM, or saline were administered to non-tumor-bearing rabbits. Serial electroretinography, optical coherence tomography (OCT) and OCT-angiography were performed. PGFM and MH both caused equivalent reductions in electroretinography amplitudes, and loss of retinal microvasculature on OCT-angiography. The pattern of retinal degeneration observed on histopathology suggested that segmental retinal toxicity associated with all melphalan formulations was due to a vitreous concentration gradient-effect. Efficacy and toxicity were assessed for PGFM given immediately (within 1 h of reconstitution) vs. 4 h after reconstitution. Immediate- and delayed-administration of PGFM showed equivalent efficacy and toxicity. In addition, we evaluated efficacy and toxicity in patients (205 eyes) with retinoblastoma vitreous seeds, who were treated with a total of 833 intravitreal injections of either MH or PGFM as standard of care. Of these, we analyzed 118 MH and 131 PGFM monotherapy injections in whom serial ERG measurements were available to model retinal toxicity. Both MH and PGFM caused reductions in electroretinography amplitudes, but with no statistical difference between formulations. Comparing those patient eyes treated exclusively with PGFM versus those treated exclusively with MH, efficacy for tumor control and globe salvage was equivalent (PGFM vs. MH: 96.2% vs. 93.8%, p = 0.56), but PGFM-treated eyes received fewer injections than MH-treated eyes (average 3.2 ± 1.9 vs. 6.4 ± 2.1 injections, p < 0.0001). Taken together, these rabbit experiments and our clinical experience in retinoblastoma patients demonstrate that MH and PGFM have equivalent efficacy and toxicity. PGFM was more stable, with no decreased efficacy or increased toxicity even 4 h after reconstitution. We therefore now use PGFM over traditional MH for our patients for intravitreal treatment of retinoblastoma. Highlights: We assessed efficacy and toxicity of two intravitreal melphalan formulations for RB. Propylene glycol free melphalan (PGFM) vs. traditional melphalan hydrochloride (MH). Used rabbit xenograft model of RB, toxicity assessment platform, and patient cohort. In rabbits and in patients, efficacy and toxicity of PGFM and MH are equivalent. Efficacy and toxicity of PGFM are the same for 4 h after reconstitution.